Pengelolaan Trafik Jaringan Menggunakan NetBalancer - Kurniawan, Bayu, Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2017)
Network traffic management is an activity performed by the administrator to manage and monitor computer network traffic. One of the application that can be used to manage network traffic is NetBalancer. NetBalancer is a network management application that displays network traffic monitoring in the form of charts and set the magnitude of division bandwidth that will be given to each Ip Address. With the application administrator can easily perform monitoring and management of network traffic because the application provides a variety of tools to help administrators manage a network. Testing is done by simulating the use NetBalancer applications in a network. From the test results using this NetBalancer application administrator can perform a wide range of traffic management bandwidthd is restricting traffic to specific IP Address, scheduling, monitoring traffic in the form of charts, and viewing record of traffic monitoring.